Innovative Recruitment Strategies: Beyond Traditional Methods in Talent Acquisition - Solihah, Rika; Emba, Emba; Suwarno, Suwarno (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research investigates the dynamics of talent acquisition and performance enhancement within PT. Java Wood Industry, focusing on the effectiveness of innovative recruitment strategies compared to traditional methods. Employing a quantitative research design, data was collected from a sample of 89 employees using random sampling techniques. Path analysis, utilizing Smart PLS as the analytical tool, was conducted to examine the direct and indirect effects of Training and Development Programs, Leadership Styles, Employee Engagement, and Employee Performance. The findings reveal significant direct effects of Training and Development Programs and Leadership Styles on both Employee Engagement and Employee Performance. Specifically, Training and Development Programs significantly influences Employee Engagement and Employee Performance, highlighting the crucial role of investing in employee skill enhancement. While Leadership Styles directly influences Employee Performance, its indirect effect through Employee Engagement was found to be statistically insignificant. These findings underscore the importance of adopting a holistic approach that integrates training and development initiatives with effective leadership practices to optimize employee engagement and performance. Overall, the research provides valuable insights for strategic decision-making and organizational policies aimed at enhancing workforce effectiveness and maintaining competitiveness in the wood industry.